Geometrical confinement controls the asymmetric patterning of brachyury in cultures of pluripotent cells - Blin, Guillaume (Development, 2018)
Diffusible signals are known to orchestrate patterning during embryogenesis, yet diffusion is sensitive to noise. The fact that embryogenesis is remarkably robust suggests that additional layers of regulation reinforce patterning. Here, we demonstrate that geometrical confinement orchestrates the spatial organisation of initially randomly positioned subpopulations of spontaneously differentiating mouse embryonic stem cells. We use micropatterning in combination with pharmacological manipulations and quantitative imaging to dissociate the multiple effects of geometry. We show that the positioning of a pre-streak-like population marked by brachyury (T) is decoupled from the size of its population, and that breaking radial symmetry of patterns imposes polarised patterning. We provide evidence for a model in which the overall level of diffusible signals together with the history of the cell culture define the number of T(+) cells, whereas geometrical constraints guide patterning in a multi-step process involving a differential response of the cells to multicellular spatial organisation. Our work provides a framework for investigating robustness of patterning and provides insights into how to guide symmetry-breaking events in aggregates of pluripotent cells.